Social Research and Disability: Developing Inclusive Research Spaces for Disabled Researchers - Burke, Ciaran; Byrne, Bronagh (Sociological Futures, 2021)
Social Research and Disability argues that the contemporary rules of sociological methods outlined in numerous research methods texts make a number of assumptions concerning the researcher including ambulance, sight, hearing and speech. In short, the disabled researcher is not considered when outlining the requirements of particular methods. Drawing upon these considerations, the volume emphasizes how disabled researchers negotiate the empirical process, in light of disability, whilst retaining the scientific rigour of the method. It also considers the negative consequences arising from disabled researchers' attempts at "passing" and the benefits that can emerge from a reflexive approach to the method. This innovative and original text will, for the first time, bring together research-active academics, who identify as being disabled, to consider experiences of being disabled within a largely ableist academy, as well as strategies employed and issues faced when conducting empirical research. The driving force of this volume is to provide the blueprints for bringing how we conduct social research to the same standards and vision as to how the social world is understood: multi-faceted and intersectional. To this end, this edited collection advocates for a sociological future that values the presence of disabled researchers and normalizes research methods that are inclusive and accessible. The interdisciplinary focus of Social Research and Disability offers a uniquely broad primary market. This volume will be of interest not only to the student market but also to established academics within the social sciences.